Developing intercultural citizenship education in the language classroom and beyond - Porto, Melina; Byram, Michael (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
In this article we argue that the aims and objectives of foreign language teaching can and should be combined with those of education for citizenship. We call this intercultural citizenship, which others refer to as world, global or cosmopolitan citizenship. We begin by explaining the purposes of foreign language teaching and then introduce the notion of criticality in education systems. We also analyse the notion of education for citizenship and focus upon its potential for encouraging learners to identify with groups of people taking action beyond the limits of the state and its boundaries. Finally, we illustrate intercultural citizenship in practice.